Avaliação in vitro da rugosidade superficial de resinas compostas após escovação simulada com diferentes dentifrícios - Monteiro, Bruna (2014)
Aim: Evaluate, in vitro, the surface roughness of two composite resins submitted to a simulated wear test with three different dentifrices, applying simulated periods of six months, one year and two years of tooth brushing. Materials and Methods: Thirty-six samples of Z350XT and 36 samples of Empress Direct were built and randomly divided into three groups (n=12) according to the dentifrice used (Colgate Total 12 Clean Mint [CT12] (control), Colgate Sensitive Pro-Alívio [CS], Oral B Pro-saúde Whitening [OBW]). The samples were submitted to 5,000, 10,000 or 20,000 cycles of simulated tooth brushing. After each simulated period, the surface roughness of the samples was measured using a roughness tester. Results: According to three-way ANOVA, dentifrice (p=0.044) and period (p=0.000) were significant. There was no significance for the composite resin factor (p=0.381) and for the interaction (p>0.05). CT12 presented the lower surface roughness (0.269 μm), not differing statistically from CS (0.300 μm). The highest surface roughness was obtained for OBW (0.390 μm), not differing statistically from CS. The higher value was obtained after 20,000 cycles (0.584 μm) of simulated tooth brushing, differing statistically from the other two periods. Conclusions: Z350 XT and Empress Direct presented similar surface roughness after all cycles of simulated tooth brushing. The surface roughness of the composites increased with brushing time. The whitening toothpaste OBW caused higher surface roughness in both composite resins.